Conference Record of Thirty-Second Asilomar Conference on Signals, Systems and Computers (Cat. No.98CH36284)
DOI: 10.1109/acssc.1998.750909
|View full text |Cite
|
Sign up to set email alerts
|

Image recognition in single-scale and multiscale decoders

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Methods (11) (12) showed that human observers can recognize and respond to image contents at bit-rates of 0.05 to 0.1 bpp, using the SPIHT algorithm, for many natural image classes. These results suggest that it is important for algorithm designers to consider very low bit rates for fast browsing tasks and wireless Internet access.…”
Section: Resultsmentioning
confidence: 99%
“…Methods (11) (12) showed that human observers can recognize and respond to image contents at bit-rates of 0.05 to 0.1 bpp, using the SPIHT algorithm, for many natural image classes. These results suggest that it is important for algorithm designers to consider very low bit rates for fast browsing tasks and wireless Internet access.…”
Section: Resultsmentioning
confidence: 99%
“…In this work we are primarily interested in the low end of the bit rate progression, where recognition is likely to take place, rather than the high-rate, high-quality end. Our work in [20], [21] showed that human observers can recognize and respond to image content at bit rates of 0.05 to 0.1 bpp, using the SPIHT algorithm, for many natural image classes. These results suggest that it is important for algorithm designers to consider very low bit rates when designing compression algorithms for fast browsing tasks and wireless Internet access.…”
Section: Resultsmentioning
confidence: 99%
“…The approach established by this investigation promises improvement upon state of the art wavelet decompression techniques for a wide range of applications, including audio denoising (Schremmer, Haenselmann, and Bömers 2001), sea clutter noise reduction for radar proximity fusing (Noel and Szu 1998), signal compression (Saito 1994), object detection (Zhu and Schwartz 2002), fingerprint compression (Bradley, Brislawn, and Hopper 1993), image denoising (Chang, Yu, and Vetterli 1998) , image enhancement (Wang, Wu, Castleman, and Xiong 2001), image recognition (Schilling, Cosman, and Berry 1998), and speech recognition (Long and Datta 1998).…”
Section: Applications Of the New Technology And Future Researchmentioning
confidence: 99%